Evaluación de la calidad del agua del río Zamora en el tramo Las Pitas - Florencia, mediante modelación matemática para periodos de estiaje - Castillo Freire, Melissa Nohelya (2024)
Due to inadequate infrastructure, the vital functions of urban rivers are at risk from pollution generated by domestic and economic-productive wastewater discharges. Keeping these functions in tact will require developing tools that provide detailed information on the transport and transformation of pollutants in water, which are a fundamental aspect of supporting environmental management that aims to safeguard and restore the quality of urban rivers. This study focuses on evaluating the water quality of the Zamora River, specifically in the Las Pitas - Florencia sector, through the application of mathematical modeling during the dry season. For this purpose, 19 effluents of the river were characterized (12 discharges and 7 streams), and 4 control points were selected along the course of the river. Physicochemical parameters such as dissolved oxygen (DO), biochemical oxygen demand (BOD), ammonium (NH4 +) and temperature were measured, in addition to conductivity, salinity and turbidity. In order to calibrate the model of BOD, NH4, and DO, the average values obtained were integrated into the general pollutant transport equation solved by the Euler method to achieve acceptable errors of 8.19%, 5.21%, and 4.51%, respectively. The analysis revealed a progressive degradation of river quality, with decreases in DO to 4.75 mg/L and increases in BOD to 84.63 mg/L and NH4 to 11.90 mg/L, affecting the aquatic balance. As a result, the Zamora River possesses significant levels of contamination, including discharges such as MP1, MP6, MP14, and MP16, which exceed the maximum limits allowed by the TULSMA and which must be controlled and managed in an appropriate manner.